O discurso da memória em Vermelho amargo. Uma leitura semiótica - Pereira, Luiz Henrique (2017)
The object of analysis of this research is the book Vermelho amargo (2011) by Bartolomeu Campos de Queirós, which we have analyzed based on the theoretical framework of French Semiotics. We applied elements from the generative process of meaning, the tensive concept of event and the theoretical-methodological model of analysis of the autobiographical discourse as proposed by Mariana Luz Pessoa de Barros(2015). Queirós, a Brazilian contemporary writer, was posthumously awarded for this autobiographical short novel, which presents, in a fragmentary way, the narrator’s childhood, predominantly marked by the precocious death of his mother and by the contentious relationship with his stepmother. We aim to analyze the narrator's memory, in order to observe the degree of sensitive and intelligible engagement he establishes with what he remembers, and also, the adult narrator’s and the boy’s narrative and pathemic paths. The matter at hand is to unveil if the records of his childhood constitute themselves as event-memory or past event-memory based on the classification elaborated by De Barros (2015). Our hypothesis is that there is in the story a prevalence of a sensitive engagement from the narrator towards his memories, that is, the memories in general are constructed as event-memories. As a result, we observed that the death of his mother happens as a tensive event, which takes the subject abruptly from a state of conjunction with his value-object, the mother and, therefore, a state of existential fulfillment to a state of disjunction, which, consequently, leaves him in a state of existential emptiness. Thus, as a subject of the enunciate, he only suffers the event of the loss of his mother without understanding what is going on during this stage of his life, a suffering state that affects him until the present of the narration and that he manifests by the memory materialized by the report that constitutes the work. Therefore, as the subject is modulated by different passions, its narration is mainly permeated by the sensitive.